E-HRM : digital approaches, directions & applications - Thite, Mohan (London ; New York : Routledge, 2019)
As with other parts of business, technology is having a profound effect on the world of work and management of human resources. Technology is a key enabler for faster, cheaper and better delivery of HR services and in some cases can have a transformational as well as unintended negative effect. Designed for the digital era, e-HRM is one of the first textbooks on these developments. It incorporates the most current and important HR technology related topics in four distinct parts under one umbrella, written by leading scholars and practitioners drawn from across the world. All the chapters have a uniform structure and pay equal attention to theory and practice with an applied focus. Learning resources of the book include chapter-wide learning objectives, case studies, debates on related burning issues, and the companion website includes lecture slides and a question bank.
Foreword & forward thinking on digital HR / Dave Ulrich, Rensis Likert Professor, Ross School of Business, University of Michigan and Partner, The RBL Group -- Electronic/digital HRM : a primer / Mohan Thite -- Key approaches to e-HRM -- Strategic management approach to technology-enabled HRM / Mark L. Lengnick-Hall, Cynthia A. Lengnick-Hall & Derrick McIver -- Soft systems thinking approach to e-HRM project management / Mohan Thite & NMK Bhatta -- Agile approach to e-HRM project management / NMK Bhatta & Mohan Thite -- Key directions in e-HRM -- Big data & e-HRM / Tobias M. Scholz -- HR metrics & analystics / Martin R. Edwards -- Cloud computing & e-HRM / Vinit Ghosh and Nachiketa Tripathi -- Social media & e-HRM / Christopher J. Hartwell -- Gamification & e-HRM / Tobias M. Scholz -- E-HRM applications -- E-talent management / Sharna Wiblen -- E-recruitment & selection / Anna B. Holm & Lars Haahr -- E-performance & reward management / Kent V. Rondeau -- E-learning & development / Charissa Tan -- Problems & perspectives -- Strategic evaluation of e-HRM / Ralf Burchach -- Information security & privacy in e-HRM / Shankar Subramaniyan, Mohan Thite & S Sampathkumar -- Future directions of electronic/digital HRM / Mohan Thite -- Index.
Includes bibliographical references and index.
Keywords: Personnel management -- Information technology; Personnel management -- Data processing; Employee selection -- Information technology